The diversity of aquatic insects surrounding the gold mining areas of central sulawesi and their relation with mercury levels and water quality - Hasriyanty Hasriyanty; Alam Anshary; Shahabuddin Saleh; Mohammad Yunus; Flora Pasaru (Perhimpunan Entomologi Indonesia, 2022)
Human activities may influence the diversity of aquatic insects in rivers. This study aims to assess the diversity of aquatic insects and their relation with mercury levels and water quality along rivers located near the gold mine in Poboya, Central Sulawesi. The insects were collected at six locations based on human activity levels. At each site, the mercury level of water was measured using atomic absorption spectrophotometry (AAS). In addition, water temperature, acidity, dissolved oxygen, and total dissolved solids were determined. The study recorded 23 species of aquatic insects belonging to 7 orders and 14 families. Mercury levels in the rivers did not exceed the threshold except at two sites and did not affect aquatic insects’ diversity. The diversity of aquatic insects, however, tends to decrease downstream. The diversity of aquatic insects, particularly the Ephemeroptera, Plecoptera, and Trichoptera orders, tended to be higher at the higher dissolved oxygen sites.